PEMIKIRAN GENDER QURAISH SHIHAB DALAM TAFSIR AL-MISHBAH - Syarifatun Nafsi (Manthiq, 2016)
Abstract: Opinions Of Quraish Shihab On Gender In The Book Of Tafsir Al-Mishbah. Gender  has become a hot topic now a day among  the academicians. Equality of men  and women always echoed both in the domestic sphere, as well as in international community. Qur’an as the main guidelines of Muslims who upholds justice, equality and  opportunities for work for both men  and  women. But some times  there  misconception among the contra  people and scapegoated Qur’an as the cause of their unequality in the community, especially  the Muslim community. This at least from the perspective of feminist non-Muslims. Therefore, this paper describes the thinking of Quraish  Shihab - as one  of the commentators in Indonesia - which  insists that Islam upholds the principles of justice, and condemned the arbitrary behavior toward women. This paper also discusses how Quraish  Shihab  interpret gender equality  through  the  interpretation of the  verses  relating  to the  creation of male and female  and male headship in the family. As a result, Quraish Shihab tend not to equate and fully align between men and women. Although similar and equally in his capacity as a human being and a servant of God and in the social life of the community, but in the role and function do not have to match exactly. Differences in the roles and  functions  of this is a relationship that is functionally  complementary to each  other  as equal partners, so as to create a system and relationship harmony towards piety together.